Launching work orders into production of wood enterprise with the multi-criteria decision-making method - Oblak, Leon (Zbornik gozdarstva in lesarstva, 2007)
Quality information is crucial for planning and running of production in wood industry companies. Information of crucial importance is the following: quality in the production process according to work orders and types of product, the information on the missing materials i.e. constituent parts according to projects i.e. work orders and the information on launching work orders into production. The method of multi-criteria decision-making was used for determining the order of launching group products into production. We studied three main criteria: market factors, organisation-production factors and economic factors. For computer support, we chose the computer programme DEXi, which represents the framework of the expert system for multi-criteria decision-making.
Keywords: lesna industrija; organizacija dela; planiranje; večkriterijsko odločanje; vodenje